Evaluación de la reducción del daño de formación causado por incrustaciones de carbonato de calcio mediante la inyección de productos verdes como fluido de estimulación en un campo ubicado en la Cuenca de Llanos Orientales (2022)
To remedy the formation damage caused by inorganic scale, stimulation treatments are carried out with generally acid fluids, which generate new major operational and environmental problems. Therefore, a new chelating agent, glutamic acid-diacetic acid (GLDA), has been developed with favorable results in carbonate and sandstone formations. With GLDA, commercial fluids such as Dissolvine® StimWellTM have been innovated, demonstrating in the laboratory and field the removal and prevention of inorganic scales.